Nurses' Performance as a Mediator Between Nurses' Fatigue and Patient Safety Culture: A Structural Equation Model Analysis - Monireh al‐Sadat Mirahmadi Niri; Zahra Khademian; Mozhgan Rivaz (Nursing Open)
ABSTRACT Aim To determine the relationships among nurses' fatigue, nurses' performance and patient safety culture. Design Cross‐sectional study. Methods A multicentre study was conducted with 308 nurses working in 14 medical and surgical wards from four teaching hospitals in Iran. The sampling method was stratified with a proportional allocation. Data were collected via a demographic form, the Occupational Fatigue/Exhaustion Recovery (OFER‐15), the Nurse Performance Instrument (NPI) and the Hospital Survey on Patient Safety Culture (HSOPSC). The data were analysed via structural equation modelling (SEM). Results Nurse fatigue was significantly inversely related to performance and patient safety culture (p < 0.001). Path analysis revealed that each unit of reducing nurses' fatigue improved patients' safety culture by 0.286 units and that each unit of improved nurse performance improved patients' safety culture by 0.360 units. Additionally, each one‐unit increase in a nurse's fatigue could decrease his or her performance by 0.860 units. SEM analysis confirmed the mediating effect of nurses' performance on the relationship between their level of fatigue and patient safety culture. Practice Implications The proposed model can assist nursing managers and healthcare policymakers in developing practical strategies to mitigate and reduce nurses' fatigue and, consequently, improve nurses' performance and patient safety. Patient or Public Contribution All participants contributed to this research by completing self‐reported scales.